The performance of legal transactions as a way to optimize the jurisdictional provision (Research, Society and Development, 2020)
This paper sought to analyze the innovations brought by the "New" Code of Civil Procedure and its impacts on legal practice, especially the Institute of Procedural Legal Affairs as a means of accelerating the progress of ongoing legal claims and of increasingly evidencing the influence of principles predominantly of Private Law on rules of Public Law, all this focusing on the rapid aspect that the CPC sought to incorporate into the Brazilian legal system. In addition, in methodological terms, research was used in doctrines, legislation and scientific articles that deal with the same theme, based on an abstract analysis to reach a concrete conclusion on the topic discussed here. Finally, it was concluded that the Atypical Legal Transactions, provided for by the general clause of article 190 of the CPC, are little used in practice, given the lack of awareness, on the part of lawyers, about the existence of such institutes, as well as the lack of interest of those in complying with the principle of cooperation, expressly provided for in CPC/2015, which ends up not contributing to one of the main objectives of the new code, namely: to reduce the bureaucracy of the process, with the consequent reduction of claims already in progress, and to ease the burden imposed on courts today.